Clinical Effect of Endoscopic Vidian Neurectomy on Bronchial Asthma Outcomes in Patients with Coexisting Refractory Allergic Rhinitis and Asthma. Issue 3 (May 2018) - Ai, Jingang; Xie, Zuozhong; Qing, Xiang; Li, Wei; Liu, Honghui; Wang, Tiansheng; Tan, Guolin
Background: The prevalence of both allergic rhinitis and bronchial asthma is high throughout the world; their mutual influence on each other has been documented in many studies. However, studies regarding surgical intervention are limited. Objective: To evaluate the clinical significance of endoscopic vidian neurectomy on bronchial asthma outcomes in patients with coexisting refractory allergic rhinitis and asthma. Methods: A total of 109 patients with moderate to severe persistent intractable allergic rhinitis and mild/moderate asthma were allocated to the bilateral endoscopic vidian neurectomy group (group 1) or conservative medication group (group 2) according to the patients' self-selection. The Rhinoconjunctivitis Quality of Life Questionnaire, Visual Analog Scale, Asthma Quality of Life Questionnaire, Total Asthma Symptom Score, and medication scores were evaluated at six months, one year, and three years after undergoing the initial treatments. Multivariate analysis was performed to determine which triggers of asthma attacks were associated with improved asthma outcomes in patients. Results: Ninety-five patients were followed up for at least three years. Postoperative scores of Rhinoconjunctivitis Quality of Life Questionnaire and Visual Analog Scale were significantly lower than preoperative scores during follow-up in group 1 and were significantly lower than those of group 2. Postoperative scores of Asthma Quality of Life Questionnaire at the three follow-up time points were higher than the preoperative scores in group 1. The Total Asthma Symptom Score was not significantly decreased in group 1. The medication scores for allergic rhinitis and asthma were gradually reduced after surgery. At the end of the follow-up, the improvement rates for allergic rhinitis and asthma were 90.6% and 45.3%, respectively. Asthma outcomes were significantly improved by controlling rhinitis symptoms in patients whose asthma attacks were induced by "rhinitis onset" or "weather change." Conclusion: Controlling allergic rhinitis symptoms by bilateral endoscopic vidian neurectomy can significantly improve asthma outcomes in patients whose asthma attacks are induced by rhinitis onset and/or cold air.